Companion rats (Rattus norvegicus) with cutaneous lesions: a retrospective study of 470 cases at two university veterinary teaching hospitals (1985–2018). Issue 3 (8th March 2019) - White, Stephen D.; Bourdeau, Patrick J.; Brément, Thomas; Bruet, Vincent; Gimenez‐Acosta, Carmen; Guzman, David S.‐M.; Paul‐Murphy, Joanne; Hawkins, Michelle G.
Abstract : Background: Rats are popular companion animals that are often presented to veterinarians for treatment of skin diseases. However, descriptions of dermatoses in rats have primarily been limited to case reports and text books. Hypothesis/Objectives: To document skin diseases and their prevalence in companion rats examined in northern California, USA and Nantes, France and to investigate predilections for the most common conditions over a 33 year or 15 year period, respectively. Animals: Four hundred and seventy rats from two hospital populations met the inclusion criteria. Methods and materials: A retrospective study was performed by searching computerized medical records of rats seen at the School of Veterinary Medicine at University of California, Davis (UCD), USA from 1 January 1985 to 1 January 2018 using the key words "skin" and "dermatitis". The medical records of rats presenting to Ecole Nationale Vétérinaire, Agroalimentaire et de l'Alimentation Nantes‐Atlantique (ONIRIS), France from 1995 to 2016 were reviewed for evidence of skin disease. The presence of lesions as noted in the key search words for the UCD records were used as the inclusion criteria for both institutions. Results: Of 494 rats examined at UCD, 231 (47%) had skin disease, with neoplasia the most common diagnosis. Of the 619 rats examined at ONIRIS, 239 (39%) had skin disease, with ectoparasitism being the most common diagnosis. Conclusions and clinical importance: Cutaneous conditions in companion rats are common. Clinicians should include a dermatological examination when examining these rodents, especially in regard to neoplasia, ectoparasites and pyoderma. Abstract : Background – Rats are popular companion animals that are often presented to veterinarians for treatment of skin diseases. However, descriptions of dermatoses in rats have primarily been limited to case reports and text books.Hypothesis/Objectives – To document skin diseases and their prevalence in companion rats examined in northern California, USA and Nantes, France and to investigate predilections for the most common conditions over a 33 year or 15 year period, respectively.Conclusions and clinical importance – Cutaneous conditions in companion rats are common. Clinicians should include a dermatological examination when examining these rodents, especially in regard to neoplasia, ectoparasites and pyoderma.